Wheat policy reform in Egypt: adjustment of local markets and options for future reforms - Kherallah, Mylene; Lofgren, Hans; Gruhn, Peter; Reeder, Meyra M. (International Food Policy Research Institute, 2000)
Many developing countries are in transition from a state-dominated to a more market-oriented economy. Because agriculture is of primary importance in most developing countries,the state is usually heavily involved in both input and output markets and in controlling prices and trade. However, concerns that market liberalization will result in higher consumer food prices and hurt the poor means that many countries, such as Egypt, have, at best, undertaken only partial agricultural sector reforms. It has been argued that such concerns are unwarranted and that further market liberalization is not only needed, but achievable without increasing impoverishment. IFPRI Research Report 115 sheds light on these critical issues through an analysis of wheat policy reform in Egypt.